Survey of foreign assets and liabilities in Nigeria 2011 report - Mohammed M. Tumala; Olufemi I. Ajibola; Babatunde S. Omotosho; Oladipupo A. Baruwa (CBN Journal of Applied Statistics, 2012)
The 2011 survey of foreign assets and liabilities (SOFAL) of enterprises in Nigeria was conducted in June/July 2012 by the Statistics Department of the Central Bank of Nigeria (CBN) in conjunction with the Nigerian Export Processing Zone Authority, Nigerian Investment Promotion Commission and other collaborating agencies. The survey covered large establishments numbering 320 across the country. A total of 275 completed questionnaires were retrieved and analyzed indicating a response rate of 85.9 per cent. The survey instrument was designed to capture cross border transactions/investments of the respondents during 2010 and 2011. Available data from survey returns showed that total foreign claims on the Nigerian economy (liabilities) as at end 2011 rose to N12,729.69 billion from N11,681.32 billion recorded in 2010. A breakdown of the figures showed that 74.8 per cent came in the form of direct investment, while portfolio investment and other capital flows accounted for 10.3 and 14.9 per cent, respectively. The European Union countries accounted for 54.9 per cent of the total inflow, and are followed by other Africa countries with 15.8 per cent. A breakdown in terms of recipient sectors of inward capital flows to Nigeria revealed that the extractive industries sector ranked highest with 49.4 per cent and is followed by manufacturing, which received 29.1 per cent. Total stock of outward investment as at end 2011 was N2,377.03 billion as against N2,500.14 in 2010. In 2011, Outward direct investment dominated with 84.1 per cent of the total, while Africa countries were the preferred investment destination for Nigerian enterprises receiving 93.3 per cent of the total outflow mostly by the Nigeria's banking industry. The survey also indicated a decline in investment flow to the economic free zones around the country.
Keywords: 330